2011
DOI: 10.1088/0034-4885/74/12/124506
|View full text |Cite
|
Sign up to set email alerts
|

In-plane electronic anisotropy of underdoped ‘122’ Fe-arsenide superconductors revealed by measurements of detwinned single crystals

Abstract: The parent phases of the Fe-arsenide superconductors harbor an antiferromagnetic ground state. Significantly, the Néel transition is either preceded or accompanied by a structural transition that breaks the four fold symmetry of the high-temperature lattice. Borrowing language from the field of soft condensed matter physics, this broken discrete rotational symmetry is widely referred to as an Ising nematic phase transition. Understanding the origin of this effect is a key component of a complete theoretical de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
322
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(351 citation statements)
references
References 99 publications
(224 reference statements)
28
322
1
Order By: Relevance
“…Extensive experiments have confirmed that nematic order exists in almost all FeSCs [2][3][4][5][13][14][15][16][17]. In most cases, the nematic order sets in at a temperature T n slightly higher than the critical temperature of magnetic order T m [4,6,10,18,19]. Usually, the magnetic order is generated by a stripe-type SDW, and possesses two characteristic vectors Q X = (π, 0) and Q Y = (0, π) in the Brillouin zone of the iron square lattice, which relate to the spin operator S(r) in the form S(r) = M X,Y e iQX,Y ·r [12,20].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Extensive experiments have confirmed that nematic order exists in almost all FeSCs [2][3][4][5][13][14][15][16][17]. In most cases, the nematic order sets in at a temperature T n slightly higher than the critical temperature of magnetic order T m [4,6,10,18,19]. Usually, the magnetic order is generated by a stripe-type SDW, and possesses two characteristic vectors Q X = (π, 0) and Q Y = (0, π) in the Brillouin zone of the iron square lattice, which relate to the spin operator S(r) in the form S(r) = M X,Y e iQX,Y ·r [12,20].…”
Section: Introductionmentioning
confidence: 95%
“…This stripe SDW breaks the discrete lattice rotational symmetry by selecting out only one of the two characteristic vectors Q X and Q Y , preserving the C 2 symmetry [6,8,10,12]. Because the nematic order and SDW order coexist over a large part of the global phase diagram, it is widely believed [3][4][5][6][8][9][10][11][12] that the nematic order is actually induced by the fluctuation of magnetic order.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that for T ≤37 K, when the current returns along a resistive branch back to the SC state at a return current I r , a pronounced hysteresis of IVCs demonstrates a Josephson-junction-like behavior [9]. However, the single crystal was confirmed to be of high quality in previous work [14], and we selected the optimally-doped Ba 0.5 K 0.5 Fe 2 As 2 which should not have a nematic state as the under-doped state [19], thus grains or twin boundaries can be also ruled out. In addition, the micro-device has well-designed geometry as shown in the inset of Fig.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%